Interest rate swaps and economic exposure - Gautam Goswami; Milind Shrikhande (Federal Reserve Bank of Atlanta, 1997)
The interest rate swap market has grown rapidly. Since the inception of the swap market in 1981, the outstanding notional principal of interest rate swaps has reached a level of 12.81 trillion in 1995. Recent surveys indicate that interest rate swaps are the most commonly used interest rate derivative by nonfinancial firms and that nonfinancial firms are major users of interest rate swaps. In this paper, we provide an economic rationale for the use of interest rate swaps by such nonfinancial firms. In a global economy, given the floating exchange rate regime, nonfinancial firms face economic exposure in the presence of foreign competition. Asymmetric information about economic exposure leads to mispricing of the firms' debt, and the firm chooses either short-term or long-term debt to minimize the cost of debt. We show that when there is a favorable (unfavorable) exchange rate shock, an exposed firm chooses short-term (long-term) debt together with fixed-for-floating (floating-for-fixed) interest rate swaps. Given interest rate expectations, interest rate swaps enable the firm to minimize the cost of fixed or floating rate debt.
Keywords: 330; Interest rates; International finance; Risk; Swaps (Finance)